HAMBATAN DAN PELUANG PENDIDIKAN ISLAM DALAM KONTEKS MODERN: (Obstacles and Opportunities of Islamic Education in a Modern Context) - Moh Safik Al Mubarok; Fikri Maulana (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2025)
This article examines the obstacles and opportunities facing Islamic education in the modern context. Islamic education stands at the crossroads of tradition and modernity, requiring adaptation to technological developments and globalization. Key obstacles include how to maintain core religious values ​​in an increasingly secular and fast-paced environment. However, within these obstacles, there are also opportunities to use technology as a tool for the wider dissemination and understanding of Islam. The article also explores efforts to improve the quality of Islamic education that is inclusive and relevant in modern society.